Vapers exhibit similar subjective nicotine dependence but lower nicotine reinforcing value compared to smokers. (April 2021) - Rycroft, N.; Hogarth, L.; MacKillop, J.; Dawkins, L.
Highlights: Dependency to nicotine was compared in smokers and vapers. Behavioural economics tasks revealed higher sensitivity to costs amongst vapers. Self-report scales highlight lack of equivalency between how products are used. Nicotine may have higher reinforcing value for smokers than vapers. Abstract: Introduction: E-cigarette use has increased rapidly over the last 10 years, mostly among smokers and ex-smokers. Although there may be some degree of dependency on nicotine via e-cigarette use, the nature of this dependency is poorly understood. The aim of this paper is to use tasks from behavioural economics to compare the value that smokers place on tobacco cigarettes to the value that vapers place on e-cigarettes. Method: Exclusive current smokers (n = 25) and vapers (n = 20) attended one session where they completed the Cigarette/e-cigarette Dependence Scale, the Cigarette/e-cigarette Purchasing Task (CPT) and the Concurrent Choice Task (CCT). The CPT requires participants to indicate how many puffs of their chosen product they would purchase at increasing price points. The CCT requires participants to choose between earning a money point or a point towards a cigarette/e-cigarette after being presented with a neutral, money or cigarette/e-cigarette cue. Results: Overall scores on the self-report scales suggest a comparable level of dependency between smokers and vapers. The CPT revealed that vapers are more sensitive than smokers to escalating costs as consumption declined as costs increased. On the CCT, when primed with money, vapers showed a decrease in choosing e-cigarettes. Conclusion: These findings suggest that, on behavioural economic tasks, tobacco cigarettes have a higher relative value than e-cigarettes. Vapers appear to place a lower limit on what they will spend to access e-cigarettes and more readily choose money over e-cigarette puffs when primed by money cues.